The Combined Gravity Model GOCO05c - Pail, Roland; Gruber, Thomas; Fecher, Thomas; GOCO Project Team (GFZ Data Services, 2016)
Abstract GOCO05c is a static global combined gravity field model up to d/o 720. It has been elaborated by the GOCO Group (TU Munich, Bonn University, TU Graz, Austrian Academy of Sciences, University Bern). GOCO05c is a combination model based on the satellite-only gravity field model GOCO05s and several gravity anomaly datasets, constituting a global 15'x15' data grid. The combination is carried out in term of full normal equation systems.Contributing Institutions are: (1) TU Muenchen, DE, Institute of Astronomical and Physical Geodesy; (2) University of Bonn, DE, Institute of Geodesy and Geoinformation; (3) TU Graz, AU, Institute of Theoretical and Satellite Geodesy; (4) Austrian Academy of Sciences, Space Research Institute, and (5) University of Bern, CH, Astronomical Institute Other Global 15’x15’ data grid: Region (Source): Number of data cellsArctic (ArcGP Group): 44522Australia (Curtin University):11170Canada (NRCan):19259Europe (IfE Hanover):15625Oceans (DTU Space): 691818South America (NGA): 24818USA (NGA): 12895For the remaining land areas (Central America, Asia, Africa, Antarctica) fill-in datasets were used: Data (Source): Number of data cells NIMA96 (DMA/GSFC): 110594GOCO05s (GOCO Group): 106099 (band-limited gravity anomalies)RWI_TOIS2012 (KIT): 117737 (topographic anomalies)GOCO05c should not be used for geophysical applications in fill-in regions, because its high frequency part in fill-in regions resulted from simple synthetic numeric forward modelling of topographic information.